Tindak Tutur Ilokusi dalam Video “Mencoba menjadi Tunanetra dalam Sehari” pada Kanal Youtube Froyonion dan Kelayakannya sebagai Bahan Ajar Pembelajaran Teks Tanggapan (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Youtube social media is still one of the forms of communication media that is widely used in society, which of course there are many speech acts that follow it. This research is motivated by the relationship between communication in society which is accompanied by the many illocutionary speech acts used by people in videos uploaded on Youtube social media. In addition, this study aims to describe the illocutionary speech acts in the video "Becoming Blind in a Day" from the Froyonion Youtube channel and its suitability as teaching materials for learning response texts. This study is a type of qualitative descriptive research. The source of this research is the video "Becoming Blind in a Day" from the Froyonion Youtube channel which was uploaded on January 31, 2020. The data in this study are transcripts of speech in the form of sentences that indicate the presence of illocutionary speech acts in the video "Becoming Blind in a Day" from the Froyonion Youtube channel. The data collection techniques used by the author are listening techniques and note-taking techniques. The analysis technique used is to transcribe the audio on the video into written form, identify and analyze the form of speech, and make a conclusion regarding the illocutionary speech act, as well as a conclusion on its suitability as a teaching material for learning response texts in the video "Becoming Blind in a Day" from the Froyonion Youtube channel. The results of this study indicate the presence of five types of illocutionary speech acts in the video with the percentage of the amount of data obtained (a) 24.4% representative, (b) 37.9% directive, (c) 3.4% commissive, (d) 34.6% expressive, and (e) 1.7% declarative. The results of the analysis of speech acts in the video "Becoming Blind in a Day" from the Froyonion Youtube channel are suitable for use as teaching materials for learning response texts in line with the CP (Learning Achievements) in the reading and viewing elements in the Merdeka Curriculum. From this study, it is hoped that it can be used as teaching materials for learning response texts and also as a reference for various language activities.